2020
DOI: 10.1111/poms.13141
|View full text |Cite
|
Sign up to set email alerts
|

Does the Office of Patient Experience Matter in Improving Delivery of Care?

Abstract: T his research examines the performance benefits of the Office of Patient Experience (OPX), a new administrative innovation in the health care industry. OPX is an independent structure within a hospital, having its own annual budget and full-time staff, and is responsible for improving patient experience during the hospital stay. We specifically investigate the effectiveness of OPXs in improving experiential quality (EQ), measured as the quality of interactions between hospital's caregivers and patients. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 120 publications
0
5
0
Order By: Relevance
“…Hospitals that focused on process management tended to improve clinical quality, but sometimes at the expense of experiential quality. State legislation initially exacerbated this trade‐off by focusing only on clinical quality, but, over time, legislation led to improvements in both quality metrics (see also Sharma et al (2020)). Another example is also from healthcare: Lee et al (2020) found that reducing government payments to hospitals with poor outcomes led to both intended and unintended consequences.…”
Section: Current State Of Relationship Between Om Research and Public Policymentioning
confidence: 99%
“…Hospitals that focused on process management tended to improve clinical quality, but sometimes at the expense of experiential quality. State legislation initially exacerbated this trade‐off by focusing only on clinical quality, but, over time, legislation led to improvements in both quality metrics (see also Sharma et al (2020)). Another example is also from healthcare: Lee et al (2020) found that reducing government payments to hospitals with poor outcomes led to both intended and unintended consequences.…”
Section: Current State Of Relationship Between Om Research and Public Policymentioning
confidence: 99%
“…We added this performance dimension because, in healthcare contexts, especially those that involve high patient–caregiver interactions, patients' perceptions of care are not always compatible with their health outcomes (Berry Jaeker & Tucker, 2020; Kang, Shah, & Dowd, 2017). At the same time, patients who report higher satisfaction levels would better absorb and use information about post‐surgery care, increasing their chances of better health outcomes (Nair, Nicolae, & Narasimhan, 2013; Sharma, Chandrasekaran, & Bendoly, 2020). Thus, we analyzed the impact of the process redesign by comparing before and after scores on the HCAHPS (Centers for Medicare and Medicaid Services (CMS), 2019) for the kidney transplant unit, and with respect to a control group.…”
Section: Efficacy Of the Process Redesignmentioning
confidence: 99%
“…In addition, hospitals have also set aside resources for patient experience management, such as the Office of Patient Experience (OPX) with designated budget and staff (Merlino & Raman, 2013). The creation of OPX and similar patient experience units allows hospitals to identify and implement best patient experience practices, to analyze HCAHPS (Hospital Consumer Assessment of Healthcare Providers and Systems) and other patient sentimental data, and to provide training to physicians and staff members to fix problems with patient experience (Sharma et al, 2020). From the OL perspective, accumulating patient experience data allows hospitals to map the patient journey better and standardize touchpoints across the continuum from initial consultation to inpatient stay to post-discharge and follow-up visits (Minemyer, 2018).…”
Section: The Role Of Market Competitionmentioning
confidence: 99%